2010
DOI: 10.1007/s00508-009-1291-7
|View full text |Cite
|
Sign up to set email alerts
|

The impact and safety of preoperative oral or intravenous carbohydrate administration versus fasting in colorectal surgery – a randomized controlled trial

Abstract: Preoperative fasting does not confer any benefit or advantage for surgical patients. In contrast, consumption of an appropriate potion composed of water, minerals and carbohydrates offers some protection against surgical trauma in terms of metabolic status, cardiac function and psychosomatic status. Peroral intake shortly before surgery did not increase gastric residual volume and was not associated with any risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
84
1
11

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(112 citation statements)
references
References 31 publications
(34 reference statements)
4
84
1
11
Order By: Relevance
“…However, it has been shown that, during the advanced stages, the disease can induce a reduction of serum total cholesterol levels [78]. Kaska et al [79] had evaluated the effects of a preoperative fasting period in CRC patients, observing no clinical benefit. Conversely, intake of nutrients seems to be a protective factor against surgical trauma.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…However, it has been shown that, during the advanced stages, the disease can induce a reduction of serum total cholesterol levels [78]. Kaska et al [79] had evaluated the effects of a preoperative fasting period in CRC patients, observing no clinical benefit. Conversely, intake of nutrients seems to be a protective factor against surgical trauma.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…The intake of liquid without residue, whether or not enriched with carbohydrates, as well as gastric emptying were tested in various studies [2,8,9]. The use of carbohydrates allowed an early insulin response, similar to that occurring after ingestion of a meal [3] and delivery of liquid with added maltodextrin (not necessarily all carbohydrates), even for diabetic patients, seemed to be in good conditions until 2 hours before surgery, improving the welfare of the patient and reducing the sensation of hunger and thirst, in addition to postoperative insulin resistance [10].…”
Section: See Also Original Article On Pages 7-17mentioning
confidence: 99%
“…Starvation also compromises the physiological response to hemorrhage and infection (Brady et al, 2003;Nygren et al, 2001). Patients receiving oral preoperative carbohydrate loading are more likely to have physiological postoperative insulin levels compared with those receiving glucose via the intravenous route and those fasting overnight and not receiving any carbohydrate loading (Kaska et al, 2010). In an ERAS protocol, patients are typically allowed clear fluids up to two hours before the anesthetic and routinely "loaded" with oral carbohydrate and protein drinks and symbiotics preoperatively.…”
Section: Minimal Preoperative Starvationmentioning
confidence: 99%